1999
DOI: 10.1007/s004150050484
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral reductions of hippocampal volume, glucose metabolism, and Wada hemispheric memory performance are related to the duration of mesial temporal lobe epilepsy

Abstract: In refractory temporal lobe epilepsy (TLE) temporal lobe structures and functions are continuously or intermittently affected by abnormal brain electrical events, noxious neurochemical agents, and metabolic disturbances. There is conflicting evidence regarding the relationship between the duration of refractory mesial TLE and quantitative measures of temporal lobe functions and volumes of the hippocampi. Twenty patients (aged 28 +/- 7 years, 14 males) with an initial precipitating injury before the age of 5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 55 publications
7
48
1
2
Order By: Relevance
“…Our findings confirm and extend earlier FDG-PET studies on the distribution of hypometabolism and seizure spread in mTLE, as shown by pixel-to-pixel comparison (6), ROI-based analysis (7,33), and EEG (34). It has been argued that remote depressions of metabolism do not simply reflect regional atrophy (35).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings confirm and extend earlier FDG-PET studies on the distribution of hypometabolism and seizure spread in mTLE, as shown by pixel-to-pixel comparison (6), ROI-based analysis (7,33), and EEG (34). It has been argued that remote depressions of metabolism do not simply reflect regional atrophy (35).…”
Section: Discussionsupporting
confidence: 90%
“…In 18 of the latter (47.4%), 14,16,[20][21][22]24,30,[33][34][35][36][37][38]40,42,[50][51][52] no statistical approaches were implemented to correct for the effects of age. Although the remaining studies addressed aging, no consistent method was chosen: 3 reported no significant effects of age on morphometric measures in controls, 15,32,48 3 found no effect of age or no effect of age at epilepsy onset in patients, 19,29,53 2 corrected for age at onset, 18,28 5 corrected for age in patients, 17,26,47,49,54 4 utilized MRI measures adjusted for age 13,31,39,46 (based on regression models derived from controls), 1 calculated epilepsy duration/age ratios, 23 2 statistically compared chronological age effects between patients and controls. 41,45 Among the longitudinal studies, 3 were singlecohort studies of patients without controls (interscan interval ranging from 2.3 to 3.4 years 27,41,44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hippocampal damage is often bilateral in patients with unilateral temporal lobe epilepsy by clinical and neurophysiological criteria (Babb, 1991;Jokeit et al, 1999;Araú jo et al, 2006). Furthermore, SE can lead to bilateral CA3 damage in humans (Fujikawa et al, 2000) and in animal models, transforming the contralateral hippocampus into an independent epileptogenic focus, capable of generating spontaneous and evoked seizures (Araki et al, 2002;Khalilov et al, 2003).…”
Section: Discussionmentioning
confidence: 99%